2015
DOI: 10.1136/bcr-2014-208199
|View full text |Cite
|
Sign up to set email alerts
|

A prominent ‘A’ notch in the pulmonary valve M mode-one more cause of the same

Abstract: SUMMARYThe M mode echocardiogram is not the main priority, during routine echocardiographic evaluation now-a-days. However, there are still a few classical conditions where this remains instructive and educative. One such situation is the presence of an 'a' wave in the pulmonary valve M mode tracing in normals and it's absence in pulmonary hypertension. In valvular pulmonary stenosis we expect a deeper 'a' wave. We describe one more cause of a prominent 'a' wave in the pulmonary valve M mode. We describe this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have reported the presence of an 'a'-wave notch in the pulmonary valve Mmode tracing in normal and its absence in PH. 19,20 In our current study, patients with LSN/MSN had higher IVRT and shorter PAcT compared with those in the NN group. As pulmonary pressure increases, peak velocity occurs earlier in systole and late systolic notching is then often present.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Previous studies have reported the presence of an 'a'-wave notch in the pulmonary valve Mmode tracing in normal and its absence in PH. 19,20 In our current study, patients with LSN/MSN had higher IVRT and shorter PAcT compared with those in the NN group. As pulmonary pressure increases, peak velocity occurs earlier in systole and late systolic notching is then often present.…”
Section: Discussionmentioning
confidence: 47%
“…Not only the Doppler notching of the PA Doppler‐flow profile, but also the notch in the M‐mode echocardiogram is related to the hemodynamics. Previous studies have reported the presence of an 'a'‐wave notch in the pulmonary valve M‐mode tracing in normal and its absence in PH …”
Section: Discussionmentioning
confidence: 99%